Physician clinical decision support system prompts and administration of subsequent doses of HPV vaccine: A randomized clinical trial. Issue 31 (18th July 2019) - Wilkinson, Tracey A.; Dixon, Brian E.; Xiao, Shan; Tu, Wanzhu; Lindsay, Brianna; Sheley, Meena; Dugan, Tamara; Church, Abby; Downs, Stephen M.; Zimet, Gregory
Highlights: Completion of the human papilloma virus (HPV) vaccination schedule remain low. Physician Clinical Decision Support systems can be utilized to provide automated reminders. This study showed increased rates of subsequent HPV vaccine, although not significant. Multifaceted approaches are needed to examine the efficacy of computer-based reminders. Abstract: Background: HPV vaccine is effective in preventing several cancers and anogenital warts, yet rates of HPV vaccination series completion in the United States are low. A primary reason identified by parents for vaccinating children against HPV is a health care provider's recommendation. Although most clinicians embrace vaccine recommendations, they are not always carried out evenly and subsequent HPV vaccines are missed. Methods: Using an electronic health records-based decision support system (CHICA) clinicians were randomized to either usual practice or to receive an automated reminder to recommend the 2nd or 3rd dose of HPV vaccine. The reminder was delivered to clinicians of all intervention group eligible adolescents who had already initiated the vaccine series. Logistic regression models with generalized estimating equations were used for data analysis. Results: A total of 1285 clinical encounters were observed across 29 randomized pediatric providers over a 13-month time frame (50.7% control group, 49.3% intervention group). Overall, patients were 44.9% female, 59.4% Black, 22.1% Hispanic, and 48.8% were ages 11–12 yrs. Within the control group, 421 (64.7%) received a subsequent HPV vaccine, compared to 481 (75.9%) (OR: 1.72, (95% CI 1.35–2.19)). Adjusted analysis showed no difference between the groups (aOR 1.52 (95% CI 0.88–2.62)) or when examined by age (11-12yrs aOR 1.66, (95% CI 0.79–3.48)) and 13-17yrs (aOR 1.19, (95% CI 0.76–1.85)) or gender female (aOR 1.39 (95% CI 0.71–2.72)) and males (aOR 1.67 (95% CI 0.95–2.92)). When results were stratified by both age and gender, there was similarly no statistically significant effect between the two groups. Conclusions: Automated physician reminders for subsequent 2nd and 3rd doses of HPV vaccination were used. Despite increased rates of vaccination in the intervention group, the differences did not reach the level of statistical significance. Future studies with multifaceted approaches may be needed to examine the efficacy of computer-based reminders. Clinical Trial Registration: NCT02558803, "HPV Vaccination: Evaluation of Reminder Prompts for Doses 2 & 3".